The effects of a virtual reality–based islamic spiritual nursing intervention: Ma’rifat Syukur Qanaah (MSQ-VR) on self-acceptance and quality of life among women with breast cancer - Desi Ariyana Rahayu; Tintin Sukartini; Abu Bakar; Chia-Jung Hsieh (Pediomaternal Nursing Journal, 2026)
Introduction: Self-acceptance is a fundamental psychological resource that enables women with breast cancer to adapt to the physical and emotional burden caused by the disease. Interventions integrating Islamic spiritual nursing into immersive VR remain limited despite growing evidence supporting virtual reality (VR) in supportive cancer care. Objective: This study aimed to evaluate the effectiveness of the MSQ-VR in improving self-acceptance among women with breast cancer, as well as to examine the correlation between self-acceptance and quality of life. Methods: A quasi-experimental pre-posttest control group study was carried out among women with breast cancer receiving chemotherapy. Respondents were assigned to either an intervention group receiving standard nursing care plus the MSQ-VR or a control group receiving standard nursing care only (each containing 40 patients). Self-acceptance and quality of life were assessed using the Psychological Adjustment to Illness Scale (PAIS) and the World Health Organization Quality of Life (WHOQOL) instrument over 6 weeks. Group differences were analyzed using the Mann-Whitney test, while the relationship between self-acceptance and quality of life was examined using the Wilcoxon test. Results: Women who received the MSQ-VR intervention showed significantly greater improvements in self-acceptance (P-value < .001). Significant improvements were observed in several dimensions of self-acceptance, including self-love despite illness, acceptance of disease-related suffering, compassion toward others, and personal growth. Furthermore, self-acceptance was positively correlated with quality of life as evidenced by r = .467 and P-value ≤ .05. This result suggested that patients with higher levels of self-acceptance experienced better well-being. Conclusion: The MSQ-VR intervention effectively enhanced self-acceptance among women with breast cancer. The positive association between self-acceptance and quality of life showed that strengthening spiritual adaptation through an immersive VR-based nursing intervention improved psychosocial well-being. MSQ-VR represented a culturally responsive and technology-assisted method that could complement supportive oncology nursing for Muslim women with breast cancer. Keywords: breast cancer; islamic spiritual nursing intervention; self-acceptance; quality of life; virtual reality